2020
DOI: 10.1029/2019tc005841
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lithospheric Mantle Scars and Rheology on Intraplate Deformation and Orogenesis: Insights From Tectonic Analog Models

Abstract: Structural heterogeneities in the deep lithosphere have been identified as an important factor in crustal tectonics, particularly where inherited deep zones of weakness may initiate orogenesis in continent interiors. Aside from structural heterogeneity, the rheological strength of the lithosphere may also have a primary role affecting the kinematics of deformation in the lithosphere. To investigate the interplay of rheology and preexisting structures, we designed a set of physical scaled analog experiments for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This observation illustrates the impact of ancient and inherited structures on the location of crustal deformation. Recent analogue experiments show that pre-existing weakness zone in the lithosphere will accommodate the regional stress through localized brittle deformation in the upper crust, while the absence of pre-existing structure results in a more distributed deformation at the surface (Santimano & Pysklywec, 2020). These pre-existing structures can either be ancient sutures between units, or have developed during past orogenic events (Vauchez et al, 1998).…”
Section: Lateral Control From Inherited Structuresmentioning
confidence: 99%
“…This observation illustrates the impact of ancient and inherited structures on the location of crustal deformation. Recent analogue experiments show that pre-existing weakness zone in the lithosphere will accommodate the regional stress through localized brittle deformation in the upper crust, while the absence of pre-existing structure results in a more distributed deformation at the surface (Santimano & Pysklywec, 2020). These pre-existing structures can either be ancient sutures between units, or have developed during past orogenic events (Vauchez et al, 1998).…”
Section: Lateral Control From Inherited Structuresmentioning
confidence: 99%
“…Based on analogue modeling (Autin et al., 2013; Henza et al., 2010; McClay & White, 1995; Morley et al., 2004; Santimano & Pysklywec, 2020; Zwaan et al., 2019), numerical modeling (Brune & Autin, 2013; Corti et al., 2007; Deng et al., 2017; Heron et al., 2016), and detailed interpretations of cross sections (Phillips et al., 2016; Y. Xie et al., 2015; Ye et al., 2018, 2020), it has been shown that pre‐existing structures are more prone to initiating brittle failure than forming new faults during new tectonic events. In natural examples (Henstra et al., 2019; Morley et al., 2004; Tong & Yin, 2011) or experimental models (Deng et al., 2017; McClay & White, 1995; Tong, Meng, et al., 2009; Zhou & Qi, 1999), pre‐existing structures are known to be key factors controlling the tectonic evolution and structural deformation pattern of the overlying strata (Autin et al., 2013; Bellahsen et al., 2006; Bladon et al., 2015; Calignano et al., 2017; Corti et al., 2007, 2013; Henza et al., 2010; McClay & White, 1995; Molnar et al., 2017; Samsu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no thermal adjustment of the brittle and viscous layer during deformation, the thinning of layers only occurs through mechanical processes (Schellart & Strak, 2016). As in previous work (Calignano et al, 2017;Santimano & Pysklywec, 2020;Sokoutis & Willingshofer, 2011;Zwaan et al, 2019), the effect of the thermal has been introduced into our models by the presence of strength variations with depth. Finally, by changing the stretching direction of the tow motors of the apparatus, the extension direction changed in Qiongdongnan Basin is represented.…”
Section: Basic Assumptions and Simplificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental results consistently highlight the dependence of strain localization and locus of deformation on the viscosity of the ductile lithospheric mantle and thus its strength, despite the lateral homogenous nature of the ductile mantle lithosphere. For the effect of lateral strength variations in the lithospheric mantle the reader is referred to Calignano et al (2015) or Santimano and Pysklywec (2020). The rheology of the mantle lithosphere has a strong effect on the distribution of deformation, such that deformation localizes within the oceanic lithosphere with a low strength in the mantle layer, whereas it localizes at the OCT in all other cases (lithospheres with intermediate and high ductile mantle viscosity, Figs.…”
Section: Controlling Parameters For Passive Margin Instabilitymentioning
confidence: 99%